Impact of product design and innovation on competitive advantage in the South African aftermarket wheel industry - Ebrahim, Muzammil (My University, 2012)
This study found that there is interesting potential in the South African aftermarket wheels industry, despite its distinctiveness from international markets such as the United States of America. This research has shown that product design and innovation are two of the key factors, largely because through these elements of strategy firms can achieve differentiation from their competitors. Another key finding is that product design and innovation are used to directly affect the product characteristics of aftermarket wheels and their perceived value to the customer, in particular individuality, recognition and status. Improving effectiveness along these lines therefore leads to creation and sustainability of competitive advantage for companies in this industry. Research has shown that for luxury products and niche markets, such as aftermarket wheels, these factors are particularly important, and these findings are confirmed in the South African study. The empirical research was conducted at a case site, Racing Hart Concepts, with supplementary data gathering among key stakeholders, such as customers, competitors and suppliers. In summary, the research conducted suggests that fulfilling the esteem needs for status and individuality of the customer, providing an aesthetically appealing product, at a competitive price and within the highest quality standards are important. At least two of these aspects, aesthetic appeal and excellent quality can be achieved largely through effective wheel design and innovation activities. The impact of wheel design and innovation activities however extends beyond just the final product; it also has implications on achieving brand trust and loyalty, positive consumer perceptions of the product and the ability to overcome some of the key challenges facing companies in this industry in South Africa. The study addressed the implications of these findings for firms operating in this niche market in South Africa and identified areas for future research.
MBA thesis - WBS
Keywords: Product design; Product innovation; Tyres; Wheel